Multi-kingdom microbial changes and their associations with the clinical characteristics in schizophrenia patients - Baoyuan Zhu; Liqin Liang; Shuhao Chen; Hehua Li; Yuanyuan Huang; Wei Wang; Heng Zhang; Jing Zhou; Dongsheng Xiong; Xiaobo Li; Junhao Li; Yuping Ning; et al. (Translational Psychiatry)
Abstract Accumulating evidence has highlighted alterations in the gut microbiome in schizophrenia (SZ); however, the role of multi-kingdom microbiota in SZ remains inadequately understood. In this study, we performed metagenomic sequencing of fecal samples from 36 SZ patients and 55 healthy controls (HC) to profile bacterial, fungal, archaeal, and viral communities, along with functional pathways. We also conducted co-occurrence network analysis to explore the relationships among differential microbial species and metabolic pathways separately. Additionally, we assessed the associations of these differential species and functional pathways with clinical characteristics. Our findings revealed significant differences in species between SZ patients and HC, identifying not only 17 bacterial species, but also 8 fungal, 26 archaeal, and 19 viral species. Functional pathway analysis revealed 21 metabolic pathways significantly altered in SZ patients, including an increase in tryptophan metabolism, while biosynthesis of amino acids was decreased. Network analysis further uncovered more complex inter-kingdom interactions in SZ patients, with specific fungal species appearing exclusively in the SZ network. Importantly, significant associations were observed between microbial species and functional pathways with clinical characteristics, including symptom severity, cognitive function, and clinical biochemical marker. For instance, the abundance of Streptococcus vestibularis was positively correlated with homocysteine levels; the ubiquinone and other terpenoid-quinone biosynthesis was positively correlated with both symptom severity and C-reactive protein. Our findings reveal the intricate microbial dysbiosis present in SZ patients, suggesting multi-kingdom microbial interactions play a crucial role in SZ patients, highlighting promising avenues for potential diagnostic and therapeutic applications.